2023
DOI: 10.31548/animal.1.2024.29
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of using different levels of mixed ligand complexes of Zinc, Manganese, and Cobalt in cow feeding

Yurij Kropyvka,
Vitalii Bomko,
Olena Tytariova

Abstract: To increase productivity and reduce the negative impact on the environment, it is necessary to investigate the most optimal ratios of organic trace elements in the diets of cows involved in the production cycle, considering their physiological state and lactation stage. The purpose of the study was to determine the economic profitability of using mixed complexes of zinc, manganese, and cobalt in the diets of dairy cows. The experiment was carried out under production conditions on Holstein cows. 100 cows were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As indicated by F. Vandenbussche et al (2022), several vaccinia-like recombinant LSDVs were identified in Kazakhstan and the neighbouring region of China in 2017-2019. Previously, mass vaccination of animals against nodular dermatitis (Lumpivax) was carried out in Kazakhstan (Kropyvka et al, 2024). LSDV was transmitted between animals.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by F. Vandenbussche et al (2022), several vaccinia-like recombinant LSDVs were identified in Kazakhstan and the neighbouring region of China in 2017-2019. Previously, mass vaccination of animals against nodular dermatitis (Lumpivax) was carried out in Kazakhstan (Kropyvka et al, 2024). LSDV was transmitted between animals.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by F. Vandenbussche et al (2022), several vaccinia-like recombinant LSDVs were identified in Kazakhstan and the neighbouring region of China in 2017-2019. Previously, mass vaccination of animals against nodular dermatitis (Lumpivax) was carried out in Kazakhstan (Kropyvka et al, 2024). LSDV was transmitted between animals.…”
Section: Introductionmentioning
confidence: 99%